Biases from different DNA extraction methods in intestine microbiome research based on 16S rDNA sequencing: a case in the koi carp, Cyprinus carpio var. Koi. Issue 1 (17th April 2018) - Han, Zhuoran; Sun, Jingfeng; Lv, Aijun; Wang, Anli
Abstract: This study examined the technical bias associated with different DNA extraction methods used in microbiome research. Three methods were used to extract genomic DNA from the same intestinal microbiota sample that was taken from the koi carp Cyprinus carpio var. koi, after which their microbial diversity and community structure were investigated on the basis of a 16S rDNA high‐throughput sequencing analysis. Biased results were observed in relation to the number of reads, alpha diversity indexes and taxonomic composition among the three DNA extraction protocols. A total of 1, 381 OTUs from the intestinal bacteria were obtained, with 852, 759, and 698 OTUs acquired, using the Lysozyme and Ultrasonic Lysis method, Zirmil‐beating Cell Disruption method, and a QIAamp Fast DNA Stool Mini Kit, respectively. Additionally, 336 OTUs were commonly acquired, using the three methods. The results showed that the alpha diversity indexes (Rarefaction, Shannon, and Chao1) of the community that were determined using the Lysozyme and Ultrasonic Lysis method were higher than those obtained with the Zirmil‐beating Cell Disruption method, while the Zirmil method results were higher than those measured, using the QIAamp Fast DNA Stool Mini Kit. Moreover, all the major phyla (ratio>1%) could be identified with all three DNA extraction methods, but the phyla present at a lower abundance (ratio <1%) could not. Similar findings were observed at the genus level. Taken together, these findings indicated that the bias observed in the results about the community structure occurred primarily in OTUs with a lower abundance. The results of this study demonstrate that possible bias exists in community analyses, and researchers should therefore be conservative when drawing conclusions about community structures based on the currently available DNA extraction methods. Abstract : This study examined the technical bias associated with different DNA extraction methods used in microbiome research. Three methods were used to extract genomic DNA from the same intestinal microbiota sample that was taken from the koi carp Cyprinus carpio var. koi, after which their microbial diversity and community structure were investigated on the basis of a 16S rDNA high‐throughput sequencing analysis. Biased results were observed in relation to the number of reads, alpha diversity indexes and taxonomic composition among the three DNA extraction protocols.